2021
DOI: 10.3389/fped.2021.659492
|View full text |Cite
|
Sign up to set email alerts
|

The Cost-Effectiveness of Congenital Adrenal Hyperplasia Newborn Screening in Brazil: A Comparison Between Screened and Unscreened Cohorts

Abstract: Background: Newborn screening for congenital adrenal hyperplasia (CAH-NBS) is not yet a worldwide consensus, in part due to inconclusive evidence regarding cost-effectiveness because the analysis requires an understanding of the short- and long-term costs of care associated with delayed diagnosis.Objective: The present study aimed to conduct a cost-effectiveness analysis (CEA) to compare the costs associated with CAH-NBS and clinical diagnosis.Methods: A decision model comparing the two strategies was tested b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…A study conducted in the US estimated a benefit to cost ratio for G-6PDD screening ranging from 1.38–3.42 using quality-adjusted life year (QALY) methodology [ 57 ]. The reported studies on the cost effectiveness of newborn screening for CAH is conducted by comparing the cost in screened and unscreened CAH patients [ 58 , 59 , 60 , 61 ]. The benefit to cost ratio of newborn screening in India that we have calculated is much higher than the already reported studies of other countries, confirming that the implementation of newborn screening in India will not be an economic burden but raise the standard of health quality.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in the US estimated a benefit to cost ratio for G-6PDD screening ranging from 1.38–3.42 using quality-adjusted life year (QALY) methodology [ 57 ]. The reported studies on the cost effectiveness of newborn screening for CAH is conducted by comparing the cost in screened and unscreened CAH patients [ 58 , 59 , 60 , 61 ]. The benefit to cost ratio of newborn screening in India that we have calculated is much higher than the already reported studies of other countries, confirming that the implementation of newborn screening in India will not be an economic burden but raise the standard of health quality.…”
Section: Discussionmentioning
confidence: 99%
“…The timeline of the NBS is becoming earlier worldwide because of increasing numbers of inborn errors of metabolism added to the screening panel, requiring immediate intervention [17], and in the U.S. the recommended age in days when the first results were obtained should be seven days of life [18]. The median age at the time of positive screening results differs among countries-from 6 days in Japan [16] to 8.7 days in Sweden [19], 13 days in Texas [20] and 17 days in Brazil [21]. In Lithuania, the main reason for the delay of diagnosis was the delay in delivery of the NBS cards to the laboratory, clearly having significant implications and should be targeted to improve the clinical usefulness and effectiveness of the screening.…”
Section: Discussionmentioning
confidence: 99%
“…43 Data from Sri Lanka, 4 where the incidence of congenital hypothyroidism is similar to India, showed that the benefit far outweighs the cost of screening (benefit-to-cost ratio of 3.60). Similarly, the screening strategies for G6PD deficiency, 44 CAH, 3 sickle cell disease, 37 and expanded strategies using tandem mass spectroscopy 45 were all found to be cost-effective.…”
Section: Cost-effectiveness Of Newborn Screeningmentioning
confidence: 93%
“…43 Data from Sri Lanka, 4 where the incidence of congenital hypothyroidism is similar to India, showed that the benefit far outweighs the cost of screening (benefit-to-cost ratio of 3.60). Similarly, the screening strategies for G6PD deficiency, 44 CAH, 3 sickle cell disease, 37 and expanded strategies using tandem mass spectroscopy 45 were all found to be cost-effective. Abbreviations: OAE, otoacoustic emissions; AABR, automated auditory brainstem response; G6PD, glucose-6-phosphate dehydrogenase; TCB, transcutaneous bilirubin; TMS, tandem mass spectroscopy; TSB, total serum bilirubin.…”
Section: Cost-effectiveness Of Newborn Screeningmentioning
confidence: 93%
See 1 more Smart Citation